Gender-based violence and COVID-19: the intersectional vulnerability of women in Maranhão - Alvares, Maria Emília Miranda; Angela Barbara Lima (Argumentum, 2021)
This essay deals with the relationship between the COVID-19 pandemic and the data provided by news outlets that mention gender-based violence in the State of Maranhão, from March to September of 2020. The pandemic has impacted on people’s lives, affecting their mental health, leading to higher levels of stress, to the aggravation of conflicts related to cohabiting and exposure to violent situations. By employing a critical analysis of the data together with the theory of the mandate of masculinity put forward by Rita Segato and the theory of racism and sexism in Brazilian culture evolved by Lélia Gonzalez, women are constantly called upon to embrace the position of carer, whilst their lives have become easily discarded during the pandemic. The article reflects on the need for a public debate on gender-based violence, in contrast to the common-sense belief that it should be treated as a private issue, a position often endorsed by the institutions of the State.